Pengaruh Pengaruh Upah Minimum, Pertumbuhan Ekonomi, Indeks Pembangunan Manusia, Dan Belanja Modal Terhadap Kemiskinan Kabupaten/Kota di Jawa Timur Tahun 2017 s/d 2021: KEMISKINAN - Ali Mauludi AC; Fadllan; Fitri Nur Rahmawati (IQTISHADIA Jurnal Ekonomi & Perbankan Syariah, 2023)
This study aims to determine the effect of minimum wages, economic growth, HDI, and capital spending on poverty in East Java districts/cities in 2017 s/d 2021. Using a quantitative approach, this research uses multiple linear analysis methods assisted by Eviews 12. Secondary data of this research sourced from the Central Bureau of Statistics, Directorate General of Fiscal Balance, Ministry of Finance, as well as other sources. This research shows the results that the minimum wage partially has a significant positive effect, while the HDI, economic growth, and capital expenditure variables have a significant negative effect on poverty in districts/cities in East Java. In addition, together the variables of minimum wages, economic growth, HDI, and capital expenditures have a significant influence on poverty in districts/cities in East Java with an effect of 99.3%